PENINGKATAN KEMAMPUAN NUMERASI PERKALIAN MELALUI MEDIA PAPER PADA SISWA KELAS III SD 4 BULUNGCANGKRING - Affan Uyung Al Farichy; Lovika Ardana Riswari; Rihayati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This classroom action research aims to improve students' numeracy skills in understanding the concept of multiplication of whole numbers 1 to 10 through the use of PAPER media "Multiplication Board" in class III of SD 4 Bulungcangkring. Numeracy skills are important for applying number concepts and counting skills in everyday life. A basic understanding that multiplication is repeated addition is an important foundation in counting skills. This study uses a Classroom Action Research (CAR) design which is carried out in 2 cycles in class III of SD 4 Bulungcangkring totaling 36 students. Each cycle consists of 4 stages including implementation, planning, observation, reflection. The data collection techniques used in this study are: interviews, observation, documentation. The results of the study showed a significant increase in students' numeracy skills. In Cycle I, students' learning completeness reached 55.6%, while in Cycle II it increased to 83.3%. These findings indicate that the application of PAPER learning media "Multiplication Board" is effective in improving students' understanding of multiplication concepts. Thus, this study concludes that the use of these media can improve students' numeracy skills in Mathematics subjects.